2011
DOI: 10.1242/dev.069336
|View full text |Cite
|
Sign up to set email alerts
|

Germ line differentiation factor Bag of Marbles is a regulator of hematopoietic progenitor maintenance during Drosophila hematopoiesis

Abstract: Bag of Marbles (Bam) is a stem cell differentiation factor in the Drosophila germ line. Here, we demonstrate that Bam has a crucial function in the lymph gland, the tissue that orchestrates the second phase of Drosophila hematopoiesis. In bam mutant larvae, depletion of hematopoietic progenitors is observed, coupled with prodigious production of differentiated hemocytes. Conversely, forced expression of Bam in the lymph gland results in expansion of prohemocytes and substantial reduction of differentiated bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 29 publications
2
51
1
Order By: Relevance
“…3G,H). Moreover, expression of an Hh-GFP reporter line (Tokusumi et al, 2011) was observed in all the PSC cells expressing either PI3K caax or TSC1 RNAi, suggesting that increased PSC size is associated with increased production of this inhibitor of prohemocyte differentiation 1715 RESEARCH REPORT Insulin/TOR in hematopoiesis Mandal et al, 2007). Together, our results indicate that increased IIS/TOR signaling not only supports Drosophila hematopoietic niche growth but also promotes its activity.…”
Section: Control Of Hematopoietic Niche Size By Iis and Tor Signalingmentioning
confidence: 67%
See 2 more Smart Citations
“…3G,H). Moreover, expression of an Hh-GFP reporter line (Tokusumi et al, 2011) was observed in all the PSC cells expressing either PI3K caax or TSC1 RNAi, suggesting that increased PSC size is associated with increased production of this inhibitor of prohemocyte differentiation 1715 RESEARCH REPORT Insulin/TOR in hematopoiesis Mandal et al, 2007). Together, our results indicate that increased IIS/TOR signaling not only supports Drosophila hematopoietic niche growth but also promotes its activity.…”
Section: Control Of Hematopoietic Niche Size By Iis and Tor Signalingmentioning
confidence: 67%
“…Notably, in contrast to what we observed in Pten larvae, increased PSC size has been associated with decreased differentiation (Mandal et al, 2007;Sinenko et al, 2009;Tokusumi et al, 2011). We thus assessed the effect of increased IIS/TOR signaling in the PSC on hemocyte differentiation.…”
Section: Control Of Hematopoietic Niche Size By Iis and Tor Signalingmentioning
confidence: 71%
See 1 more Smart Citation
“…Therefore, our data provide a new line of evidence showing distinct molecular mechanisms employed in male versus female germline stem cell differentiation pathways. However, in the lymph gland, Bam maintains hematopoietic progenitors at an undifferentiated state and bam mutation results in a reduction of hematopoietic progenitors, but an increase in differentiated hemocytes (Tokusumi et al, 2011). Therefore, in different tissues, Bam acts differently to either block or induce differentiation.…”
Section: Research Articlementioning
confidence: 99%
“…In addition, as readout for decreased Bam protein levels, we used the percentage of testes containing at least one 32-spermatocyte cyst, which reflects Bam protein levels precisely (Insco et al, 2009); the previous study used nuclear morphology (Pek et al, 2009). In hematopoietic progenitors, Bam and miR-7 function cooperatively, but bam is not a target of miR-7 (Tokusumi et al, 2011).…”
Section: Post-transcriptional Regulation Of Bam By Micrornasmentioning
confidence: 99%